TRIB3 promotes pulmonary fibrosis through inhibiting SLUG degradation by physically interacting with MDM2 - Xiaoxi Lv; Shanshan Liu; Chang Liu; Yunxuan Li; Tingting Zhang; Jie Qi; Ke Li; Fang Hua; Bing Cui; Xiaowei Zhang; Yuxin Liu; Jiaojiao Yu; et al. (Elsevier, 2023)
Pulmonary fibrosis (PF) is the pathological structure of incurable fibroproliferative lung diseases that are attributed to the repeated lung injury-caused failure of lung alveolar regeneration (LAR). Here, we report that repetitive lung damage results in a progressive accumulation of the transcriptional repressor SLUG in alveolar epithelial type II cells (AEC2s). The abnormal increased SLUG inhibits AEC2s from self-renewal and differentiation into alveolar epithelial type I cells (AEC1s). We found that the elevated SLUG represses the expression of the phosphate transporter SLC34A2 in AEC2s, which reduces intracellular phosphate and represses the phosphorylation of JNK and P38 MAPK, two critical kinases supporting LAR, leading to LAR failure. TRIB3, a stress sensor, interacts with the E3 ligase MDM2 to suppress SLUG degradation in AEC2s by impeding MDM2-catalyzed SLUG ubiquitination. Targeting SLUG degradation by disturbing the TRIB3/MDM2 interaction using a new synthetic staple peptide restores LAR capacity and exhibits potent therapeutic efficacy against experimental PF. Our study reveals a mechanism of the TRIB3-MDM2-SLUG-SLC34A2 axis causing the LAR failure in PF, which confers a potential strategy for treating patients with fibroproliferative lung diseases.